2011
DOI: 10.1007/s12034-011-0027-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gamma radiation on electrical and optical properties of (TeO2)0·9 (In2O3)0·1 thin films

Abstract: We have studied in detail the gamma radiation induced changes in the electrical properties of the (TeO 2 ) 0·9 (In 2 O 3 ) 0·1 thin films of different thicknesses, prepared by thermal evaporation in vacuum. The currentvoltage characteristics for the as-deposited and exposed thin films were analysed to obtain current versus dose plots at different applied voltages. These plots clearly show that the current increases quite linearly with the radiation dose over a wide range and that the range of doses is higher f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The decrease in band gap shows that the irradiated film causes a slightly 'red shift' in the optical spectra. This decrease in the optical band gap is basically due to the increase in the energy width of the band tails of localized states, similar observations have also been reported by other worker [17][18][19]. The absorption coefficient near the band edge shows an exponential dependence on photon energy [20]:…”
Section: Effect Of Gamma Irradiation On the Structural And Optical Prsupporting
confidence: 85%
“…The decrease in band gap shows that the irradiated film causes a slightly 'red shift' in the optical spectra. This decrease in the optical band gap is basically due to the increase in the energy width of the band tails of localized states, similar observations have also been reported by other worker [17][18][19]. The absorption coefficient near the band edge shows an exponential dependence on photon energy [20]:…”
Section: Effect Of Gamma Irradiation On the Structural And Optical Prsupporting
confidence: 85%
“…During γ-ray irradiation, the defects are created within the thin film. At the same time, the defects also get annihilated even under the normal room temperature conditions [39,40]. This creation and annihilation of defects coexist together and at higher doses of γ-ray irradiation, the number of defects created due to γ-ray irradiation equals the number of defects annihilated [40].…”
Section: Spectral Distribution Of Absorbance Of H 2 Tpp and Zntpp Thimentioning
confidence: 99%
“…Sharma and Maity [28] reported that the optical band gap was found to decrease after γ-irradiation. This decrease in the optical band gap is due to the increase in Urbach tails.…”
Section: Determination Of Transition Type Evaluation Of Optical Energ...mentioning
confidence: 99%
“…Zhu [29] supposed that ionizing radiation causes structural defects which intern leading to a change in their density upon exposure to γ-ray. The produced free electrons as a result of band-to-band transitions are trapped in ion vacancies which in turn is the cause of formation of color center leading to increase the electrical conductivity [28,29]. Therefore, the decrease in the optical band gap is essentially due to the increase in Urbach tails [30].…”
Section: Determination Of Transition Type Evaluation Of Optical Energ...mentioning
confidence: 99%